Fast electrons produced by lower hybrid wave and effects on plasma–wall interactions - Hailong Lu; Nong Xiang; Zehua Qian; Hua Yang; Miaohui Li; Manni Jia; Gen Li; Zechen Wang; Changhao Deng; Jinjin Lu; Jiamin Long (Nuclear Fusion)
Lower hybrid wave (LHW) current drive plays a crucial role in sustaining steady-state (SS) discharges on the Experimental Advanced Superconducting Tokamak (EAST). Hotspots frequently form on the wave antenna and guard limiters during SS operations. Although both experimental and theoretical studies suggest that fast electrons could be responsible for these hotspots, the underlying mechanisms of fast electron generation under typical EAST operational parameters and their impact on the hotspots remain unresolved. In this work, particle-in-cell simulations are used to investigate the interactions between LHWs and electrons in front of the antenna, taking into account the realistic incident power spectra and localized field effects. The results show that, due to resonance overlap, fast electrons are produced through resonant interactions between electrons and LHW components with a high parallel refractive index ( N _∥ ). The velocity distribution function in velocity space is found to significantly depend on plasma parameters near the antenna, such as q _95 , electron temperature, and input power. These fast electrons notably enhance the sheath potential on the guard limiters and increase the heat flux to the wall.